An empirical study on cultural identity measurement and its influence mechanism among heritage tourists - Fu, Yuanbo; Luo, Jian Ming (Frontiers in Psychology, 2023)
In the effort to integrate culture and tourism, an important strategy for the prosperity and sustainability of tourism, it is necessary to factor in tourists’ cultural identity and emotional interaction with cultural heritage to keep pace with the trends of cultural heritage tourism. Drawing on in-depth interviews and software such as Nvivo and Smart-PLS, this study aims to develop and verify cultural identity measures for cultural heritage tourists, construct a theoretical model of cultural identity, travel experience, place attachment, satisfaction, and revisit intention, and verify the theoretical relationship and influence between these dimensions in the Archaeological Ruins of Liangzhu City. The results show that cultural identity has a significant positive impact on travel experience and place attachment but no remarkable impact on satisfaction; travel experience has a significant positive impact on place attachment and revisit intention; place attachment has a significant positive impact on satisfaction; place attachment has a significant positive impact on revisit intention; satisfaction has a significant positive impact on revisit intention. This qualitative and quantitative research enriches the theoretical achievements concerning cultural identity among cultural heritage tourists and proposes recommendations for management practice accordingly.